Representation of New York City in Film “Ali & Ratu-Ratu Queens” - Susanto, Bella Angelina (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
The purpose of writing this analytical paper is to prove that every aspect of the film is like an example the selection of landscapes, color tones, production design, and storylines are very influential in raising an important issue which in the context of this film is the socio-economic issue that exists among Indonesian immigrants in New York City. This research is used qualitative descriptive methods and used a landscape theory approach to find point of view in this film. Based on the scene and from a theoretical point of view, the evidence in each film scene has an important role in supporting an argument to be conveyed the socio-economic gap that occurs between immigrants in New York. With the help of setting, character, and storyline in this film, is easily conclude that financial differences will always happen everywhere. The example is between the two in the film. To observing the habits and lifestyle contained in the storyline can be done by utilizing research related to the colors used in a scene to evoke the same mood. Sometimes, something that is visually beautiful and pleasing to the eye does not always convey deep feeling and vice versa. However, visuals and feelings/mood will certainly create an amazing work.